Characterization of Abiotic Stress Tolerant Rhizobia as PGPR of Mothbean, Clusterbean and Mungbean Grown in Hyper-arid Zone of Rajasthan - Mondal, H. K.; Mehta, S.; Kaur, H.; Gera, R. (International Journal of Bio-resource and Stress Management, 2017)
The present investigation was focused on isolation and in vitro characterization of high abiotic stress tolerance, PGPR traits and dinitrogen fixation efficiency among cultivable rhizobia nodulating mothbean, clusterbean and mungbean. A total of 201 rhizobial isolates were retrieved from 101 different nodule samples collected from various locations of four districts i.e. Churu, Bikaner, Jaisalmer and Barmer situated under hyper-arid zone of Rajasthan, India. Around 70% of rhizobial isolates showed steady growth at 30% of polyethylene glycol 6000 (PEG 6000) and 30% of isolates showed tolerance at 40% PEG when drought tolerance of different rhizobia were assessed. Similarly 70% of the rhizobial isolates showed luxurious growth at temperature of 40 °C and only 30% of isolates showed survival ability at 45 °C. Combined abiotic stress tolerance experiment revealed that 54 rhizobial isolates were tolerant to 30% PEG and 40 °C while only 16 isolates showed high drought tolerance of 40% PEG 6000 and high temperature tolerance at 45 °C. In vitro assessment of dinitrogen fixation efficiency showed all 54 stress tolerant isolates possessed dinitrogen fixation ability with different degrees of efficacy. Stress tolerant rhizobial isolates also harbored multiple PGPR traits like phosphate solubilization, IAA production, ammonia excretion, bacteriocin production and ACC deaminase activity. Hence, our result showed a promising percentage (30%) of different rhizobial isolates can be used further in situ trials in pot house and field conditions as high abiotic stress tolerant isolate accompanying with multiple PGPR traits for future bioinoculant production.